THE CULTIVATION OF VANILLA AND AGAR WOOD WITH AGROFORESTRY SYSTEM AS MODEL OF SUSTAINABLE FOREST MANAGEMENT IN EAST KALIMANTAN PROVINCE - Kunio, Kitai; Lahjie, Abubakar M.; Hefni, Asnan; Kristiningrum, Rochadi (Journal of Agroecology, 2015)
The objective of this study was to find out the optimum production of vanilla and the maximum increment of agar wood cultivated in an agroforestry system and to perform financial analysis to the system. This research conducted in Bukit Raya Village, Kutai Kartanegara Regency, East Kalimantan Province. Method of this research conducted by using theory of production, scientific principles to calculate the production of vanilla and the increment of agar wood by measuring the diameter and the highest of agar wood. To find out the financial worthiness by using Pay Back Period (PP), Net Present Value (NPV), Net benefit cost ratio (Net B/C) and Internal Rate of return (IRR). Results showed that the maximum production of vanilla at the age of 9 years old with a total production was 378 kg/ha, it can be harvested at the age 3 to 11 years while the increment of agar wood can be inoculated at the age 4-5 years with the age of inoculation during 2 years and gubal Agar wood can be harvested at the age 6 years to 25 years. The optimum increment of agar wood was reached at the age 15 years old with a total maximum was 14.5 m3/ha and the cultivation maintained up to 25 years because of financial reasons. The financial cultivation analysis of vanilla which combined with agar wood by using NPV, Net B/C and IRR theory at an interest rate of 15% was 54,592,000 rupiah, 1.95 and 21.5%, respectively. Equivalent annual annuity was 8,445,350 rupiah with a scale effort of 6 ha. It proved that the cultivation of vanilla and agar wood is feasible to cultivate by using Net present value, net B/C and IRR more than MAR.